Reliability of Korean Version AMS and ADAM Questionnaire - Paek, Ri-Hyang; Ri, Son-Ok; Jong, Hyang; Ko, Min-Hyok; Ri, Kyong-Il; Song, Song-Il; Yu, Kang (Medical Science Journal for Advance Research, 2025)
Context: There are number of non-English version of AMS and ADMA questionnaires tested for their validity and reliability before use in evaluation of LOH worldwide. But there has been no investigation on reliability of Korean version of AMS questionnaire and ADAM questionnaire in Korean male affected with LOH. Aim: The purpose of this study is to evaluate the reliability of Korean version of AMS questionnaire and ADAM questionnaire in Korean male patients with LOH. Patients and Methods: 959 Korean men in various age participated in the study between 2016 and 2018. The reliability of questionnaire was determined by means of Reliability analysis to calculate the Cronbach’s reliability coefficient α. Results: The reliability of Korean version AMS questionnaire was very good with 0.925 of the Cronbach’s α as well as the corrected item-total correlation of the one item above 0.3. But the Cronbach’s α of the ADAM questionnaire was 0.792 and the corrected item-total correlation of the one item was below 0.3. Conclusion: Korean version AMS questionnaire can be reliably used in Korean men but the reliability of Korean version ADAM questionnaire is not so good and it needs to be adjusted when used in Korean men. Therefore, AMS questionnaire would be preferred when we approach Korean men affected with LOH.